Predictors of persistent diarrhea in norovirus enteritis after solid organ transplantation. Issue 11 (6th October 2016) - Chong, Pearlie P.; van Duin, David; Sonderup, Jessica L.; Grant, Wendy J.; Kalil, Andre C.; Florescu, Diana F.
Abstract: Solid organ transplant (SOT) recipients may develop protracted diarrheal illness from norovirus. We performed a retrospective chart review between January 2010 and April 2014 to identify predictors of persistent diarrhea in transplant recipients with norovirus enteritis. A total of 152 SOT recipients with mean age of 31.5 years (SD 23.1) were included: 43.4% male, 34.2% pediatric patients. Allograft types were abdominal 136 (89.5%) (kidney [39.5%], liver‐small bowel [23%], other [27%]) and thoracic 16 (10.5%). The median time to diagnosis of first norovirus enteritis episode from date of transplantation was 1.7 (0.3‐5.3) years. At time of presentation, diarrhea was present in 141 (93%). Thirty percent had persistent diarrhea at 2 weeks. Hospitalization was required for treatment in 121 (80%) of episodes with the mean length of stay of 10±15.2 days. Most (91%) infections were due to norovirus genogroup II, and gastrointestinal coinfections were seen in 23 (19%) norovirus enteritis episodes. Nausea at time of diagnosis ( P =.002) and cytomegalovirus (CMV) infection in the preceding 90 days ( P =.036) were identified as independent risk factors for persistent diarrhea using univariate and multivariable logistic regression. Our study shows that nausea on presentation and prior CMV infection were associated with persistent diarrhea in patients with norovirus enteritis.